Switzerland : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This paper reviews Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Switzerland. The paper discusses that The Federal Banking Commission (CFB) is the oversight body for banks, securities dealers, and fund managers in Switzerland. The intermediaries under its control may also join a self-regulatory organization that can set minimum standards. Nevertheless, the power to specify the rules for implementing the LBA (Loi sur le blanchiment d'argent) and to enforce those rules is essentially reserved to the oversight authority.